Burr hole as a management for extra axial hematomas in a low-resource setting. (April 2023) - Suleman, Mujaheed; Tendai, Joylene; Lodhia, Jay
Abstract: Introduction and importance: In a low-resource setting, the availability of neurosurgeons and neurosurgical equipment for neurosurgery has proved to be a challenge for the management of extra-axial hematomas hence general surgeons perform burr hole surgeries for emergencies. Case presentation: We share our experience with three patients who presented with extra-axial hematomas and managed successfully in our institute with craniostomy as the surgical approach. Clinical discussion: Traumatic brain injury is a major global health burden as it is a leading cause of death among the middle-aged population. Mortality associated with brain injury is highest in low- and middle-income countries. From our experience, we had good outcome in terms of improved Glasgow Coma Scale and overall clinical status in those who underwent burr hole surgery for extra axial hematoma. Conclusion: The need for neurosurgeons in sub-Saharan Africa is high but training comes at a cost hence general surgeons can perform life-saving emergency procedures with good outcomes. Highlights: Traumatic brain injury is a major public health issue in low- and middle-income countries. The availability of neurosurgeons and neurosurgery equipment is a challenge in sub-Saharan Africa. Training and equipment for neurosurgery are costly hence general surgeons perform life-saving emergency neurosurgeries.